2022
DOI: 10.2147/copd.s374945
|View full text |Cite
|
Sign up to set email alerts
|

SWEmean of Quadriceps, a Potential Index of Complication Evaluation to Patients with Chronic Obstructive Pulmonary Disease

Abstract: To develop a potential quadriceps' index of complication evaluation for patients with chronic obstructive pulmonary disease (COPD) which is simple, convenient, and quantifiable. Patients and Methods: We conducted a prospective study of 59 patients with COPD and 56 healthy controls recruited by the Chengdu First People's Hospital. Grayscale ultrasound (US) of the rectus femoris was performed to measure thickness (RF thick ) and cross-sectional area (RF csa ). Shear wave elastography was used to determine the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The pain mainly concentrated in the knee joint and around the tibial plateau, and the quadriceps femoris had relatively less pain in the early stage of KOA. Some studies have assessed the risk of muscle weakness and sarcopenia in COPD patients by measuring the RF SWE ( Deng et al, 2021 ; Niu et al, 2022 ). The results showed that the shear modulus of patients was significantly lower than that of normal people, and the sensitivity of this index was higher than that of muscle thickness and cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pain mainly concentrated in the knee joint and around the tibial plateau, and the quadriceps femoris had relatively less pain in the early stage of KOA. Some studies have assessed the risk of muscle weakness and sarcopenia in COPD patients by measuring the RF SWE ( Deng et al, 2021 ; Niu et al, 2022 ). The results showed that the shear modulus of patients was significantly lower than that of normal people, and the sensitivity of this index was higher than that of muscle thickness and cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…Shear wave elastography (SWE) is a novel ultrasonography techniqie. It transmits and tracks shear waves to obtain Shear modulus values, and dynamically depicts the distribution of SWE in target tissues in real time ( Niu et al, 2022 ). Shear modulus value can be used to quantify local muscle stiffness ( Chalchat et al, 2022 ), and tiffness is a proxy for the force of muscle contraction ( Lin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are already many approaches for the use of ultrasound in the assessment of tissue rheological properties [ 67 ], the most widely used being the supersonic shear wave imaging (SSI) [ 68 ]. The method has so far been attributed with a variable reliability ranging between 0.67 and 0.92 (95% CI Avg , see Table 1 ) by various studies [ 33 , 40 , 41 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Objective Methods Of Muscle Tone Diagnosismentioning
confidence: 99%